Pengaruh Current Ratio (CR) Net Profit Margin (NPM) Dan Return On Asset (ROA) Terhadap Harga Saham Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun (2018-2022) - Reggina Firgie Natasya; Immas Nurhayati; Renea Shinta Aminda (CV. ITTC INDONESIA, 2024)
Stock investment is currently one of the most popular forms of investment among the public, this is because stock investment can provide much greater profits than investment in other capital market instruments. Losses that can occur when investing in shares are due to investors' lack of knowledge in minimizing the risk of loss. Investing in shares is not just about investing capital in a company, but it is necessary to carry out analysis to determine the company's performance, especially in fundamental and technical analysis. By knowing the company's fundamentals, investors can assess the company's performance so that investors can minimize risks that may occur during long-term investments. Meanwhile, by knowing technical analysis, investors can find out stock price movements, making it easier for investors to decide which securities are worth buying or selling. The fundamental factors used are the variables Current Ratio, net profit Margin, Return On Assets This research was conducted with the aim of determining the influence of the variables Current ratio, Net Profit Margin, Return on assets on share prices in the food and beverage sector listed on the Indonesia Stock Exchange in 2018-2022. This research uses a quantitative approach with a purposive sampling method. The data used is secondary data and the analysis method used is panel data regression and multiple linear regression. The results of this research show that partially the Current Ratio and Return On Asset variables have a positive effect on stock prices, while the Net Profit Margin variable has no effect on stock prices. And simultaneously the variables Current Ratio, Net Profit Margin, Return On Assets influence stock prices.